Periosteal Nerve Block Vs. Intravenous Morphine in Pain Relief of Distal Radius and Ulna Fracture; a Double-Blind Randomized Clinical Trial - Ashtari, Shadi; Hasanzadeh, Alireza; Bahmani, Alireza; Abdolrazaghnejad, Ali (Archives of Academic Emergency Medicine, 2023)
Introduction: Distal forearm fractures’ realignment and fixation is a painful procedure. This study aimed to compare the efficacy of periosteal nerve block and intravenous morphine in distal radius and ulna fractures’ pain management. Methods: In the present randomized, parallel, double-blind, controlled clinical trial, patients with distal radius or ulna fractures were divided into two groups. In the first group, for periosteal nerve block, 1% lidocaine was injected at a distance of 6 to 8 cm near the wrist from the lateral radius and medial ulna. In the second group, morphine sulfate at a dose of 0.1 mg/kg was slowly injected through the peripheral vein within 5 minutes. The visual analog scale (VAS) score was evaluated before the intervention and every 15 minutes until 90 minutes after the intervention and was compared between the two groups. Results: 75 subjects were studied (39 in the periosteal nerve block and 36 in the intravenous morphine group). There were no significant differences between the groups in terms of mean age (p = 0.384), gender distribution (p = 0.464), past medical history (p = 0.106), trauma type (p = 0.836), fracture type (p = 0.613), and baseline pain severity on VAS (p = 0.987). Both methods reduced the VAS scores during the 90 minutes of the study. The mean pain scores of the patients in the periosteal nerve block group with 2.56±1.44, 2.15±1.11, 2.66±1.26, and 3±1.27 at 15, 30, 45, and 60 minutes after the analgesic injection, respectively, were significantly lower than those of the intravenous morphine group with 4.75±1.27, 4.22±1.22, 3.97±1.27, and 4.13±1.35, respectively (p < 0.001 for all comparisons). In the present study, no local or systemic complications were observed in the periosteal nerve block group, while the complications of dyspnea, vomiting, and pruritus were reported by 5.5%, 2.8%, and 2.8%, respectively, in the intravenous morphine group. Moreover, the percentage of need for additional analgesia in the intravenous morphine group was higher than that of the periosteal nerve block group. Conclusion: In the first hour after the intervention, pain reduction in periosteal block was significantly higher than intravenous morphine administration. Also, the incidence of complications and the need for additional analgesia were lower in the periosteal block group compared to intravenous morphine administration.